Primary Onomatopoeia Found in Nursery Rhymes by Dave and Ava on Youtube - PUTU YOHANA KERTIASIH; I Dewa Ayu Devi Maharani Santika; Ni Made Verayanti Utami (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
Nowadays in daily life, people often use words to communicate with each other. The people interaction will produce a sound as an imitation of certain objects. These words and sounds are onomatopoeia. This study expects to an investigationof one types of primary onomatopoeia, from a Nursery Rhymes by Dave and Ava on YouTube. This study used the theoryproposed by Ullmann (1962:84) to identify the types of primary onomatopoeia and, the second theory of meaning is lexical meaning was analyzing by using theory of Lyon (1995:47) and contextual meaning used theory proposed by Ullmann (1962:64). The data of this study were analyzed descriptively. Observation method and note taking technique were used in collecting the data of this study. The findings presented by using the formal and informal methods. The result of this study shows that there are 12 data belong to primary onomatopoeia. Furthermore, from the two types of meaning, the lexicalmeaning become the dominant meaning of the primary onomatopoeia.